The Diplomacy of Quasi State in Territorial Disputes: Taiwan in the South China Sea - Sukmawani Bela Pertiwi; Luh Nyoman Ratih Wagiswari Kabinawa; Rangga Aditya (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to examine the diplomacy of quasi-state in a territorial dispute by using the case of Taiwan in the South China Sea. The discussion on quasi-state is not mainstream in International Relations, and thus its concept and theories are not well developed. By the rise of globalization, however, quasi-states have a more active presence and that many parties involved in conflicts which resolutions require understanding on quasi-state, including the South China Sea Disputes. This paper argues that quasi-state suffers from legal and political weaknesses, and consequently, the diplomacy of quasi-state could be examined using theories on the diplomacy of weak states which include multitrack diplomacy to deal with its legal weaknesses and hedging to deal with its political shortcomings. Employing a qualitative method based on primary and secondary sources on Taiwan evolving policy on the South China Sea, this paper found that the diplomacy of Taiwan in the South China Disputes also follows this pattern.